In Vitro Repair of Fractured Fiber-Reinforced Cusp-Replacing Composite Restorations - Willem M. M. Fennis; Cees M. Kreulen; Arzu Tezvergil; Lippo V. J. Lassila; Pekka K. Vallittu; Nico H. J. Creugers (International Journal of Dentistry)
Objective. To assess fracture resistance and failure mode of repaired fiber-reinforced composite (FRC) cusp-replacing restorations. Methods. Sixteen extracted human premolars with fractured cusp-replacing woven (Group (A)) or unidirectional (Group (B)) FRC restorations from a previous loading experiment were repaired with resin composite and loaded to fracture. Results. Differences in fracture loads between groups were not statistically significant (P=0.34). Fracture loads of repaired specimens were significantly lower than those of original specimens (P=0.02 for Group (A) and P<0.001 for Group (B)). Majority of specimens showed failure along the repaired surface. In Group (B) 89% of specimens showed intact tooth substrate after restoration fracture, while this was 28% in Group (A) (P=0.04). Conclusion. Fractured cusp-replacing FRC restorations that are repaired with resin composite show about half of fracture resistance of original restorations. Mode of failure with a base of unidirectional fibers is predominantly adhesive.